The Ability of Nano Chitosan and Bacillus subtilis (Ehrenberg) Cohn to Suppress the Growth of Alternaria porri (Ellis) Ciferri - Al Farisy, Muhammad Restu; Meliansyah, Rika; Susanto, Agus; Hersanti, Hersanti (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2024)
Purple blotch disease, caused by the fungus Alternaria porri (Ellis) Ciferri, poses a significant threat to shallot crops. Environmentally friendly control methods, such as applying nano-sized chitosan and Bacillus subtilis (Ehrenberg) Cohn, offer promising alternatives. This study aims to determine the effective concentrations of nano chitosan and B. subtilis, individually and in combination, to suppress the growth of A. porri in-vitro. The research was conducted from March to June 2024 at the Phytopathology Laboratory and Plant Protection Biotechnology Laboratory, Department of Pests and Plant Diseases, Faculty of Agriculture, Universitas Padjadjaran. A completely randomized design was employed, consisting of nine treatments with three replications each: a control treatment, B. subtilis 107 CFU/ml, 50 ppm nano chitosan, 100 ppm nano chitosan, 200 ppm nano chitosan, B. subtilis 107 CFU/ml + 50 ppm nano chitosan, B. subtilis 107 CFU/ml + 100 ppm nano chitosan, B. subtilis 107 CFU/ml + 200 ppm nano chitosan, and 80% mancozeb. The results indicated that nano chitosan at a concentration of 100 ppm was the most effective single treatment which could suppress the growth of A. porri colonies by 94% and inhibit conidia germination by 95%. Meanwhile, B. subtilis 107 CFU/ml + 100 ppm nano chitosan is the most effective mixed treatment which could suppress the growth of A. porri colonies by 84% and inhibit conidia germination by 90%.